OPTIMALISASI LITERASI SAINS PESERTA DIDIK MELALUI E-LKPD BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PENCERNAAN - Gita Dwi Ikhwati, Adelia; Faizah, Ulfi; Nafisah, Wirdatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Scientific literacy is a crucial competency for students to develop, enabling them to understand concepts and solve problems scientifically through Problem-Based Learning (PBL). However, scientific literacy achievement in Indonesia remains low, particularly regarding the digestive system a topic linked to various authentic real-world issues. Therefore, there is a need for teaching materials that foster scientific literacy, such as the PBL-based electronic student worksheet (E-LKPD) developed in this study. This research aimed to analyze the optimization of students' scientific literacy through the use of this PBL-based E-LKPD while supporting Sustainable Development Goals (SDGs) Goal 3 (Good Health and Well-being) and Goal 4 (Quality Education). The study employed the 4D research method (Define, Design, Develop, and Disseminate). Data were collected via validation sheets, implementation logs, response questionnaires, and pre- and post-test scores, all analyzed using descriptive quantitative methods. Trials were conducted with 36 Grade XI students at SMA Sunan Giri Menganti. The results indicate that the developed E-LKPD met the criteria for being highly valid, highly practical, and effective in optimizing students' scientific literacy, as evidenced by an N-Gain score of 0.75 (high category). This effectiveness is supported by E-LKPD features designed to cultivate specific scientific literacy indicators and address SDG 3 contexts: Bio-Start (formulating scientific questions), Bio-Study (developing hypotheses), Bio-Explore (conducting experiments), Bio-Present (constructing scientific arguments), and Bio-Check and Bio-Reflect (drawing accurate conclusions and evaluating results). Thus, the PBL-based E-LKPD on the digestive system is suitable as a teaching tool to optimize students' scientific literacy while supporting SDGs 3 and 4.